2019
DOI: 10.1108/ijhrh-12-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development goals and reproductive healthcare rights of internally displaced persons in India

Abstract: Purpose The internally displaced persons (IDPs) are often overlooked population, falling between the cracks of international and national commitments. Displaced women and children go through more hardship than the male counterpart, as they are frequently at greater risk and do not get adequate access to the reproductive healthcare rights; they suffer from poor health amid threats of eviction. The purpose of this paper is to look into the IDPs reproductive healthcare situation in India and sustainable developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…One of the active roles of the government and humanitarian assistance organizations is to provide adequate standards of living and social security for IDPs. This is in complete agreement with previous studies ( 21 ). Minimum Initial Service Package (MISP) is one of the standards in this regard which can be used in humanitarian settings to meet the needs of IDPs ( 48 50 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…One of the active roles of the government and humanitarian assistance organizations is to provide adequate standards of living and social security for IDPs. This is in complete agreement with previous studies ( 21 ). Minimum Initial Service Package (MISP) is one of the standards in this regard which can be used in humanitarian settings to meet the needs of IDPs ( 48 50 ).…”
Section: Discussionsupporting
confidence: 94%
“…The 11 included studies reported on reproductive health management in IPDs focusing on lack of access to certain services ( 11 – 16 ), violence against women ( 12 , 15 18 ), lack of education ( 11 , 12 , 14 , 15 , 19 , 20 ), attitude, cultural taboos, religious and community beliefs ( 17 , 19 , 20 ), human rights and dignity ( 16 , 20 , 21 ), neglected family planning ( 12 , 17 , 19 ) and unplanned pregnancy ( 11 , 14 , 17 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the active roles of the government and humanitarian assistance organizations is to provide adequate standards of living and social security for IDPs. This is in complete agreement with previous studies (21). Minimum Initial Service Package (MISP) is one of the standards in this regard which can be used in humanitarian settings to meet the needs of IDPs (48)(49)(50).…”
Section: Coordination and Collaborationsupporting
confidence: 86%
“…None of the grey literature sources met our inclusion criteria. The 11 included studies reported on reproductive health management in IPDs focusing on lack of access to certain services (11)(12)(13)(14)(15)(16), violence against women (12,(15)(16)(17)(18), lack of education (11,12,14,15,19,20), attitude, cultural taboos, religious and community beliefs (17,19,20), human rights and dignity (16,20,21), neglected family planning (12,17,19) and unplanned pregnancy (11,14,17). The main challenges were described and categorized in the field of reproductive health management in the humanitarian settings for IDPs at this stage.…”
Section: Resultsmentioning
confidence: 99%